Legal Analysis of the Determination of Substitute Heirs According to the Compilation of Islamic Law - Agustinus Jonas Sahetapy (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2024)
This writing aims to determine the position of grandchildren as substitute heirs in the Islamic inheritance system according to the Compilation of Islamic Law and the legal considerations of Judges in determining substitute heirs. The position of grandchildren as substitute heirs in the Islamic inheritance system according to the Compilation of Islamic Law based on Article 185 paragraph (1), a person can inherit because the replacement of place is the person who is replaced by his child must have died earlier than the testator and the person who is replaced by his child is an heir if he were still alive. In addition, the most important requirement is that both the actual heir and the successor heir must be Muslim. In addition, the background of the application for determination of heirs is also for the benefit of third parties who want to buy the inheritance so that to prevent problems in the future, it is necessary to determine the heirs.